Education for Emancipation: notes for trying to think the education in contexts of depersonalization and social disruption. (Rosario, Argentina, after the great crisis of 2001) - Tranier, José (Nómadas. Critical Journal of Social and Juridical Science, 2013)
At the late 60´s, a series of academic publications have been written in order to try to re-think education through an ideological, philosophical and pedagogical addressed. These critical authors asked about the role and the responsibility of education in the political action of a particular society. So, in this way of thinking, , would have to do with , , and, . We are referring here to Adorno (Education after Auschwitz); Freire (Pedagogy of the oppressed); Bourdieu (The Reproduction); and Althusser (Ideological State apparatus). All these works have been published between 1968 and 1969 and have become as major works for the educational thought. In this paper we would like to reflect about some particular issues related to education, teachers, society and students that have been taken place in the recent years in our recent history. Issues linked with some expressions and actions of made by students –and teachers- at school and leisure institutions. So, we are interested in trying to ask if these episodes would also express something regarding with a social and political fragmented space, at school, from the great crisis in Argentina, in 2001. We are interested in try to integrate them into a critical argument in order to try, as Adorno says, to contribute to a general enlightenment that provides an intellectual, cultural and social climate in which a recurrence of these kind of episodes, would no longer be possible.
Keywords: education; social disarticulation; emancipation; judeophopia